A-LIEP 2011: Core Competencies for Information Professionals of Thai Academic Libraries In the Next Decade (A.D. 2010-2019)/ Piyasuda Tanloet and Kulthida Tuamsuk - Tanloet, Piyasuda; Tuamsuk, Kulthida (2011)
This research aimed to develop core competencies framework for information professionals of Thai academic libraries in the next decade (2010-2019). The study consisted of two phases, Phase 1- the study of roles of Thai academic libraries and information professionals in the next decade and Phase 2- the development of core competencies framework conducted by using the Delphi technique. This paper presents Phase 2 of the study. The research conceptual framework on core competencies for information professionals was synthesized and adopted from several resources including Gulati, & Raina (2000); Gorman & Corbitt (2002); Abels et al.(2003); Aschoft (2004) and University of Nebraska-Lincoln Library (2007). The subject of Delphi study included 21 experts from the following three groups: 8 instructors of library and information science, 8 administrators/practitioners of academic libraries, and 5 scholars who have had active roles in the library and information professionals. Data were collected in 3 rounds and analyzed by using the median, mode and inter-quartile range. Results of the study were concluded and discussed on the three following core competencies for information professionals of Thai academic libraries in the next decade. 1) The Knowledge - consists of 8 areas including the knowledge on the foundations of information profession, information resources, information and knowledge management, information technology, library and information services, organizational management, research and user studies, and continuing education and lifelong learning. 2) The Skills – consist of 11 skills including user services, information resource management, information technology, marketing, language and communication, team working, analytical thinking, problem solving and decision making, management and planning, teaching and training, conceptual thinking, and knowledge management skills. 3) The personal attributes – consist of 7 characters including the leadership, service mind, morals and professional ethics, achievement motivation, accountability, self-management and adaptability.